ANALISA PERHITUNGAN RENCANA ANGGARAN BIAYA DAN PENERAPAN MANAJEMEN WAKTU PADA PELAKSANAAN PROYEK REHAB RUMDIS HUBDAM XVI/PATTIMURA – AMBON - Matahelumual, Mygthsico Joana; Jamlaay, Octovianus; Titaley, Henriette Dorothy (Jurusan Teknik Sipil, 2024)
The rehabilitation of the Hubdam XVI/Pattimura Ambon Official Residence was carried out as an improvement to building facilities that were damaged by the movement of the earth's plates (earthquake). Construction work consists of planning a cost budget plan to planning a project implementation schedule. This study aims to calculate the cost budget plan (RAB) and determine which work is included in the critical trajectory. The building cost budget plan (RAB), identifies each work item in the project being calculated based on the 2019 SNI analysis and applies the Critical Path Method (CPM) method. The cost budget plan (RAB) for the Hubdam XVI / Pattimura Ambon official residence rehabilitation project for the total price amount is IDR 2,725,577,390.90 rounded up to IDR 2,725,577,000.00, - and the work items that are passed through the critical path are preparation work, foundation and concrete work, roof work, ceiling work, to painting work.